Can ischemic stroke patients with mTICI of 2b achieve similar outcomes compared to those with complete recanalization following endovascular therapy? - Xu, Zunbao; Grewal, Sahibjot; Mofatteh, Mohammad; Dmytriw, Adam A.; Zhao, Dongqing; Chen, Baikeng; Chen, Haoyang; He, Wanyi; Luo, Rixin; Li, Zhenzhang; Li, Qiaowei (Frontiers in Neurology, 2024)
Background and purposeEndovascular therapy (EVT) has been used as a standard treatment method for patients with large vessel ischemic stroke within 24 h of the onset. The extent of recanalization after EVT can be assessed using the modified thrombolysis in cerebral infarction (mTICI) scale as an accepted angiographic grading system. In this study, we aimed to investigate whether patients with a mTICI grade of 2b achieve similar outcomes compared to those with complete recanalization (mTICI of 3) following EVT for acute ischemic stroke.MethodsA retrospective analysis was conducted on 196 consecutive patients who underwent EVT in a comprehensive stroke center. In the final study, 176 patients were included based on the inclusion criteria. The primary outcome was the 3-month modified Rankin Scale (mRS) of 0–2 considered as a favorable outcome, while excellent outcomes were defined as mRS scores of 0–1.ResultsOur data showed that 59.46% of patients in the mTICI 2b group achieved a favorable outcome, comparable to 58.99% observed in the mTICI 3 group (p = 0.959). Additionally, 54.05% (n = 37) of patients with mTICI 2b achieved an excellent outcome, compared to 51.80% (n = 139) in the mTICI 3 group (p = 0.807). The case fatality rates were also comparable between the groups, with 8.11% in the mTICI 2b group and 10.79% in the mTICI 3 group (p = 0.632). Overall, there were no statistically significant differences between the two groups in terms of 3-month favorable outcomes, excellent outcomes, or mortality.ConclusionSimilar 3-month outcomes can be achieved for ischemic stroke patients undergoing EVT with a mTICI grade of 2b compared to those with a mTICI grade of 3. These data can help clinicians in setting realistic expectations and making informed decisions during EVT procedures.